Cognitive deficit in children (literature review) - A. S. Avtenyuk; I. V. Makarov; D. A. Emelina; R. F. Gasanov; I. V. Kravchenko; E. S. Prokhorenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
In the review article, the authors provide the definition of the term «cognitive deficit», epidemiology and possible etiological and pathogenic pathways of child psychiatric disorders, accompanied by cognitive dysfunction, as well as experimental psychological methods which are used to diagnose cognitive deficit. Reasons which lead to cognitive deficit in children are diverse and include almost all neurodevelopmental disorders such as intellectual disability, developmental delay, autism and attention deficit and hyperactivity disorder. The prevalence of psychiatric conditions accompanied by cognitive impairment is extremely high, in spite of substantial achievement in psychopharmacology and rehabilitation. Meanwhile, preservation of human cognitive functioning is the most important mission of the heath-care system.